MANAJEMEN KURIKULUM PERGURUAN TINGGI 2025 BERBASIS OUTCOME BASED EDUCATION (OBE) - Rawis, Joulanda A. M.; Sumual, Shelty D. M.; Azhar, Yulham; Al Azhar, Baginda Z.; Pranoto, Agung (STKIP Pesisir Selatan, 2025)
Objective: This study examines the management of the 2025 Higher Education Curriculum based on Outcome-Based Education (OBE), focusing on curriculum planning, implementation, and evaluation, as well as the extent to which OBE principles are integrated into academic practices. Method: A qualitative exploratory case study approach was employed. Data were collected through in-depth interviews, participatory observations, and curriculum document analysis. Data analysis followed Miles, Huberman, and Saldaña’s Interactive Model, involving data condensation, display, and verification. Results: The findings indicate that the implementation of the OBE-based 2025 Curriculum remains in a transitional stage. While the formulation of learning outcomes (CPL) aligns with OBE standards, consistency varies across programs. Constructive alignment between CPL–CPMK–RPS is not yet optimal, learning practices remain teacher-centered, and curriculum evaluation is not fully data-driven. Institutional challenges include limited lecturer readiness, weak authentic assessment, inadequate digital infrastructure, and insufficient industry collaboration Novelty: This study offers an integrated mapping of OBE-based curriculum management by combining national policy analysis with field evidence, producing a conceptual model for strengthening systemic and sustainable curriculum implementation